Pesticides: Environmental Stressors Implicated in the Development of Central Nervous System Disorders and Neurodegeneration - Alexis Rodríguez; María Luisa Castrejón-Godínez; Nayeli Monterrosas-Brisson (Stresses, 2025)
The relationship between various central nervous system (CNS) disorders linked to pesticide exposure highlights a growing concern worldwide, as the extensive use of these compounds causes toxic effects on the CNS of non-target organisms. Reports indicate that exposure to pesticides, including carbamates, organophosphates, and pyrethroids, produces various adverse impacts on neurological function in humans, ranging from acute symptoms such as headaches and dizziness to long-term conditions leading to developmental delays in children, cognitive impairment, and neurodegenerative diseases, such as Parkinson’s and Alzheimer’s being among the most important. The scientific evidence suggests that pesticide exposure induces oxidative stress and disruptions in neurotransmission, resulting in neuronal damage and alterations in brain development. The review discusses scientific evidence of neurodegenerative disease development related to pesticide exposure, as well as alternatives to chemical pesticides used in agriculture, emphasizing Agroecological Crop Protection (ACP), which combines biological control, crop rotation, and natural predators and is presented as a practical approach to reducing reliance on pesticides. Organic farming methods, which employ natural substances and minimal input of chemicals, also offer safer alternatives. In addition, advances in biopesticides, which target specific pests without harming non-target organisms, provide promising solutions that protect the environment and human health. Pesticides are well-known environmental stressors that menace biodiversity and pose important threats to human health. Reducing pesticide use and remediating pesticide-polluted sites are urgent tasks to avoid adverse effects of pesticide exposure in non-target organisms.